ON AN EXPERIMENTAL SEED COLLECTION AND FIELD CULTURE OF KING PRAWN, PENAEUS LATISULCATUS - Kathirvel, M; Selvaraj, V (Indian Journal of Fisheries, 2011)
Early juveniles of the King prawn, Penaeiis latisulcatus Kishinouye, werecaught from the sandy barmouth area of Kovalam backwater, near Madras, duringMay-July 1986. These were successfully cultivated in an earthern pond at theMuttukadu Maricuiture Centre of the Institute for a period of 80 days supplementingbackwater clam (Meretrix casta) for feed. Over this time thefemales were found grown up and with developing ovary. The size-frequency analysisof the juveniles obtained from the wild and those reared showed agrovrth of 29-30 mm per month. The hatchery-raised postlarvae of the specieswere reared on a diet of zooplankton (copepods, rotifers and freshwater cladocerans)and moUuscan meat (boiled flesh of clam and mussel). Those reared oncopepod diet exhibited faster growth and those reared on a combination of zooplanktonand molluscan meat exhibited higher survival